Mercury toxicity and bioaccumulation: lab & field studies - Rodrigues, Andreia do Carmo Martins (2018)
This work aims to evaluate the toxicity, bioaccumulation and biomagnification of mercury and it is divided into a laboratory and a field component. The laboratory component was divided into two parts and the field component was conducted into an estuarine environment in Ria de Aveiro, Portugal. In the laboratory we started by evaluating the toxicity of mercury for different aquatic organisms, using mercury concentrations that ranged between 0.5 μg/L to 2.4 mg/L. The chosen species used in this assay to evaluate mercury toxicity were the models: Pseudokirchneriella subcapitata, Daphnia magna and Chironomus riparius and the autochthonous species: Chlorella vulgaris, Lemna minor and Daphnia longispina. Mercury showed to be toxic to all testes species, with EC50 values ranging from 7.3 μg Hg/L (immobilization test of D. longispina) to 1.58 mg Hg/L (immobilization test of the larvae of C. riparius). The assay showed that even low doses of mercury can cause significant effects at the levels of primary producers, the base of the trophic chain. In the secondary laboratorial assay, an aquatic trophic chain was simulated using the primary producer P. subcapitata, the primary consumer D. magna and the secondary consumer Danio rerio. The trophic chain mercury contamination process was initiated exposing an algae culture to inorganic mercury (10 μg Hg/L), resulting in the accumulation of 70% of the available mercury in the primary producer. The contaminated algae were then used as food supply to the specie D. magna and subsequently D. magna specimens were used as food to the secondary consumer. After 14 days of exposure D. magna accumulates 0.14 μg Hg/g, whereas the final average concentration obtained in the muscle of the fish D. rerio after 21 days was 0.27 μg Hg/g (wet weight). All test species accumulate mercury along the time of exposure; the higher biomagnification occurred from the microalgae P. subcapitata to the mircrocrustacean D. magna, enhancing the crucial role of primary producers in the bioconcentration of mercury from the water column along the trophic chain. Fieldwork was conducted in the Ria de Aveiro, in two specific sites (Cais do Bico and Barra) that were already characterized regarding dissimilar environmental mercury contamination levels. Mercury levels were evaluated in the water column (total mercury), sediments (total and organic mercury) and in juvenile fish Liza aurata inhabiting the area (total and organic mercury). Cais do Bico site, located near the source of contamination showed the highest values of total mercury: 68 ng/L in the water column, 0.19 μg/g in the sediments and 0.07 μg/g in fish. The site distant from the source of mercury (Barra) presented a great amount of organic mercury in the sediments (0.02 μg/g) and a higher percentage of organic mercury in fish muscle (96%). The study indicates that, although mercury discharges have already stopped in the end of the last century, mercury stored in sediments continues to be ressuspended to the water column, becoming bioavailable to biota. The adoption of juvenile specimens provides information on short-term variations of mercury concentrations in the environment.